Controlled clinical comparison of Isolator and BACTEC 9240 Aerobic/F resin bottle for detection of bloodstream infections. - Pohlman, J K (1995)
A controlled clinical comparison was carried out with the BACTEC 9240 Aerobic/F resin bottle and the Isolator system with adult patients suspected of having bloodstream infections. A total of 10,500 paired specimens were collected, of which 1,122 from 520 patients were positive. There were 68 false-positive BACTEC bottles; 259 positive cultures that were excluded from analysis because the bottle, the Isolator, or both failed to meet the minimum volume criterion of 8 ml of blood; and 207 positive cultures that were excluded because the isolates were found to be clinically insignificant or of indeterminate clinical significance on the basis of patient assessment. A total of 656 positive cultures from 258 patients formed the basis of the analysis. Significantly more Staphylococcus aureus isolates (P = 0.03), Staphylococcus epidermidis isolates (P = 0.03), members of the family Enterobacteriaceae (P = 0.03), and Pseudomonas aeruginosa isolates (P = 0.04) were recovered from the resin bottle, and there was no category of organism that was recovered significantly more frequently from the Isolator system. With patients receiving antibiotics at the time of blood culture, S. aureus, S. epidermidis, and gram-negative bacilli were recovered significantly more frequently from the resin bottle. No significant differences between systems were found with cultures from patients not receiving antibiotics at the time of blood culture. Only 12 clinically significant organisms were recovered from the bottle on terminal subcultures, and only 1 of these had not been previously isolated from another blood culture set (10 of the 12) or from the companion Isolator (1 of 12).(ABSTRACT TRUNCATED AT 250 WORDS)